Associations of E-Cigarette Nicotine Concentration and Subsequent Cigarette Smoking and Vaping Levels in Adolescents - Goldenson, Nicholas I. (JAMA Pediatr, 2017)
IMPORTANCE: Research indicates that e-cigarette use (vaping) among adolescents is associated with the initiation and progression of combustible cigarette smoking, yet the reasons for this association are unknown. OBJECTIVE: To evaluate whether use of e-cigarettes with higher nicotine concentrations is associated with subsequent increases in the frequency and intensity of combustible cigarette smoking and vaping. DESIGN/SETTING/PARTICIPANTS: Prospective school-based cohort; surveys were administered in Spring (baseline, 10(th) grade) and Fall (6-month follow-up, 11(th) grade) 2015 among past 30-day vapers with available nicotine concentration data (N=181) from 10 high schools in the Los Angeles, CA metropolitan area. EXPOSURE: Self-report of baseline e-cigarette nicotine concentration (i.e., none [0 mg/mL], low [1–5 mg/mL], medium [6–17 mg/mL] or high [18 mg/mL or greater]) typically used during the past 30-days. MAIN OUTCOME(S) AND MEASURE(S): Frequency of past 30-day combustible cigarette smoking and e-cigarette use (0 days [none], 1–2 days [infrequent], ≥ 3 days [frequent]) and daily smoking and vaping intensity (number of cigarettes smoked per day, number of vaping episodes per day and number of puffs per vaping episode) at 6-month follow-up. RESULTS: There were positive associations between baseline e-cigarette nicotine concentration vaped and frequent (vs. no) past 30-day combustible cigarette and e-cigarette use at follow-up. Each successive increase in nicotine concentration (none-to-low, low-to-medium, medium-to-high) was associated with a 2.26 (95% confidence interval [CI]: 1.28, 3.98) and 1.65 (95%CI: 1.09, 2.51) increase in odds of frequent smoking and vaping, respectively, after adjustment for baseline frequency of smoking and vaping and other relevant covariates. Use of high (vs. no) nicotine concentration e-cigarettes was associated with a greater number of cigarettes smoked/day at follow-up (adjusted rate ratio [95%CI] = 7.03 [6.11, 7.95]). Use of low, medium and high nicotine concentrations (vs. no nicotine) were associated with a significantly greater number of vaping episodes per day (adjusted rate ratios: 2.44–3.32) and number of puffs per vaping episode (adjusted rate ratios: 2.05–3.39) at follow-up (ps<.05). CONCLUSIONS AND RELEVANCE: The results of this study provide preliminary evidence that use of e-cigarettes with higher nicotine concentrations by youth may increase the frequency and intensity of smoking and vaping.